IMPLEMENTASI METODE GROUP INVESTIGATION DALAM MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR MAHASISWA SEJARAH DI STKIP-PGRI LUBUKLINGGAU - yeni asmara (LP4MK STKIP PGRI Lubuklinggau, 2021)
This study aims to describe the implementation of the group investigation method in improving the activities and learning outcomes of history students at STKIP-PGRI Lubuklinggau. This type of research is an action research, with the research subject being the sixth semester students. This research was conducted in two cycles in each cycle consisting of 4 (four) stages, namely planning, implementation, observation, and reflection. Data collection techniques used are test techniques using questions in the form of descriptions, and non-test techniques using observation sheets for students and lecturers. The data analysis technique used is to use a simple percentage formula to measure the learning outcomes and activities of students and lecturers. From the results of research and discussion that the implementation of the group investigation method during the lecture process can improve the activities and learning outcomes of history students in semester VI at STKIP-PGRI Lubuklinggau. This can be seen from the results of data analysis which shows an increase in classical learning outcomes in the first cycle from 55.3% to 86.95%. Student activity in the first cycle increased 68% to 85.94% after the implementation of the group investigation method.